Milk Fat Globule Membrane Alleviates Short Bowel Syndrome-Associated Liver Injury in Rats Through Inhibiting Autophagy and NLRP3 Inflammasome Activation - Yu, Zhicai; Huang, Shanshan; Li, Ying; Niu, Yang; Chen, Honghao; Wu, Jiang (Frontiers in Nutrition, 2022)
Background The milk fat globule membrane (MFGM), a tri-layer membrane structure surrounding the milk fat globule, has been shown to have immune-modulating properties. This study aimed to investigate the effects of MFGM supplementation in a rat model of short bowel syndrome (SBS) associated liver disease and its possible mechanisms. Materials and Methods Twenty one male Sprague-Dawley rats were randomly divided into three groups: Sham, SBS (underwent massive small bowel resection), and SBS+MFGM (SBS rats supplemented with 1.5 g/kg/d MFGM). Liver pathology, myeloperoxidase (MPO) staining, serum levels of aspartate aminotransferase (AST)/alanine aminotransferase (ALT), endotoxin concentration, protein expression of autophagy and nucleotide binding oligomerization domain, leucine-rich repeat and pyrin domain-containing protein 3 (NLRP3) pathway in the liver tissue were measured. Results Both SBS and SBS + MFGM groups had higher serum levels of ALT and liver endotoxin levels than the Sham group (P < 0.05), with no difference detected between each other. Compared with the SBS group, the SBS+MFGM group showed lower liver pathology scores of steatosis and inflammation, less MPO positive cells and reduced expressions of NLRP3, apoptosis-associated speck-like protein containing a CARD (ASC), Caspase-1, interleukin (IL)-1β(P < 0.05) in the liver. Additionally, the expression of Beclin-1 and microtubule-associated protein1 light chain 3(LC3) B, the fluorescence intensity of NLRP3 and LC3B in the SBS + MFGM group were lower than the SBS group (P < 0.05). The LC3B expression was positively correlated with the NLRP3 level. Conclusion Enteral supplementation of MFGM help to alleviate liver injury in SBS rats, which might be related to inhibition of aberrant activation of autophagy and NLRP3 inflammasome pathways.